Using E-Portfolio to Enhance Student’s Attitudes Towards Learning English at University College of Applied Sciences. - Al-Hidabi, Dawood Abdulmalek Yahya; Kabilan, Muhammad K.; Shakfa, Mahmoud D. (IOSR Journal of Research & Method in Education, 2019)
Attitude is considered to be an essential element of the English language learning process at tertiary level. The present study investigates the outcome of using e-portfolio to enhance students’ attitude towards English language learning at UCAS (University College of Applied Sciences) in Palestine. 60 students (30 males and 30 females) who are enrolled in English Language course (DIPL 1303) at first semester of 2014/2015 academic year were selected as a sample of this study. A Sequential Exploratory Design was used to collect qualitative and quantitative data for one semester. The findings of this study revealed that students’ attitude towards learning English changed positively after utilizing e-portfolio. This has generated several theoretical, pedagogical and policy implications for instructors, universities and researchers. Therefore, it can be concluded that integrating e-portfolio at the tertiary level would enhance students’ attitude towards English language learning and release their potentialities towards the learning process.